Video-Recording Based on Self Assessment System for Senior High School Students in Speaking Class - Nofa Silfia; Don Narius (Journal of English Language Teaching, 2012)
This paper discuss one technic English language teaching especially in Senior High School by ussing “self assessment system. The step of teaching in this technic can be one of activity and can interested students to studied English language with fun and motivated. This activity consist of two meetings, first meeting the teacher explain about self assessment and video recording. the students also discuss the expression will they use in their activity. For recording the video, the students free to record in everywhre they want and they can express all the expression. In second meeting, the students watch the recording and assess all performance or their ability in speaking English. This activity can enhance theier critical thinking and assess their friends ability. This activity are fun activity and can motivate students to speaking.Key Words: video recording, self assessment, speaking.AbstrakMakalah  ini membahas salah satu teknik pengajaran bahasa inggris khususnya bagi siswa Sekolah Menengah Atas melalui teknik “self assessment system”. Urutan kegiatan pada teknik ini dapat menjadi salah satu kegiatan yang dapat menarik minat siswa untuk belajar bahasa inggris dengan semangat dan termotivasi tanpa merasa terbebani. Kegiatan ini terdiri dari dua kali pertemuan, pada pertemuan pertama guru memberikan pengetahuan tentang self assessment dan video recording, siswa juga akan mendiskusikan ekspresi yang akan digunakan dalam kegiatan mereka. Untuk merekam drama mereka, siswa diberi kebebasan untuk memilih tempat mereka masing-mas[1]ing dan bekerja di luar jam sekolah, dan siswa bisa meng-ekpresikan diri mereka. Pertemuan kedua, siswa menonton rekaman drama mereka dan memberikan penilaian terhadap rekaman tersebut.Teknik ini diharapkan dapat bermanfaat bagi guru bahasa Inggris, sehingga menambah teknik mereka dalam pengajaran berbicara. Dan juga bagi siswa diharapkan teknik ini dapat meningkatkan kemampuan berbahasa Inggris, motivasi dan percaya diri,berfikir kritis serta siswa dapat merasa senang belajar bahasa Inggris di sekolah atau di luar lingkungan sekolah.